Pioneer Transcription Factors Initiating Gene Network Changes - Zaret, Kenneth S. (Annu Rev Genet, 2020)
Pioneer transcription factors have the intrinsic biochemical ability to scan partial DNA sequence motifs that are exposed on the surface of a nucleosome and thus access silent genes that are inaccessible to other transcription factors. Pioneer factors subsequently enable other transcription factors, nucleosome remodeling complexes, and histone modifiers to engage chromatin, thereby initiating the formation of an activating or repressive regulatory sequence. Thus, pioneer factors endow the competence for fate changes in embryonic development, are essential for cellular reprogramming, and rewire gene networks in cancer cells. Recent studies with reconstituted nucleosomes in vitro and chromatin binding in vivo reveal that pioneer factors can directly perturb nucleosome structure and chromatin accessibility in different ways. This review focuses on our current understanding of the mechanisms by which pioneer factors initiate gene network changes and will ultimately contribute to our ability to control cell fates at will.